TANGGUNG JAWAB HUKUM OPERATOR TELEPON SELULER BAGI PENGGUNA LAYANAN JASA TELEKOMUNIKASI DALAM HAL PEMOTONGAN PULSA SECARA SEPIHAK DI DENPASAR - Wahyu Widyaningrat, Ida Ayu; Supasti Dharmawan, Ni Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014, 2014)
The title of this paper is "Legal Responsibility on the User's Mobile Phone Operators ofTelecommunications Services In The Event of Cuts Unilaterally Pulses in Denpasar". The purpose ofthis writing to know the form of a purchase agreementrelating to the legal relationship between themobile phone operator by users of telecommunications services in Denpasar and as well as legalresponsibility on the user's mobile phone operators of telecommunications services in the event ofcuts unilaterally pulses in Denpasar. The research method was to wear approach laws empiricalresearch. The form of a purchase agreement relating to the legal relationship between the mobilephone operator by users of telecommunications services is oral agreement by electronicintermediaries. Legal responsibility on the user's mobile phone operators of telecommunicationsservices in the event of cuts unilaterally pulses in Denpasar is the compentation of the return pulse istruncated in accordance with Article 19 of Law Number 8 of 1999 on Consumer Protection.
Keywords: Agreement, Buying ans Selling, Operators, Users